2020
DOI: 10.1093/gerona/glaa257
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Plasma Folate and Vitamin B6 With Blood DNA Methylation Age: An Analysis of One-Carbon Metabolites in the VA Normative Aging Study

Abstract: One-carbon metabolism is an important contributor to aging-related diseases; nevertheless, relationships of one-carbon metabolites with novel DNA methylation-based measures of biological aging remain poorly characterized. We examined relationships of one-carbon metabolites with three DNA methylation-based measures of biological aging: DNAmAge, GrimAge, and PhenoAge. We measured plasma levels of four common one-carbon metabolites (vitamin B6, vitamin B12, folate, and homocysteine) in 715 VA Normative Aging Stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…Previous studies have proposed there are several factors influencing Hcy levels such as age, sex, BMI, smoking, coffee drinking, poor nutrition, vitamin intake, folate, and ultraviolet radiation [ 44 , 45 ]. Previous studies have reported differences in Hcy levels between male and female schizophrenia patients, although the results have been inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have proposed there are several factors influencing Hcy levels such as age, sex, BMI, smoking, coffee drinking, poor nutrition, vitamin intake, folate, and ultraviolet radiation [ 44 , 45 ]. Previous studies have reported differences in Hcy levels between male and female schizophrenia patients, although the results have been inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have proposed there are several factors in uencing Hcy levels such as age, sex, BMI, smoking, coffee drinking, poor nutrition, vitamin intake, folate, and ultraviolet radiation [39,40]. Previous studies have reported differences in Hcy levels between male and female schizophrenia patients, although the results have been inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, it is possible that events in the mother’s childhood could have effect during pregnancy and more specifically on her future newborns’ outcomes. Nwanaji-Enwerem et al verified whether preconception maternal ACE could cause stress-related physiologic reprogramming that might result in child health changes, causing intrinsic epigenetic acceleration age, due to intergenerational effects ( Nwanaji-Enwerem et al, 2021b ) ( Figure 3 ). Describing ACEs experienced by mothers during their childhood and epigenetic aging of their children at 7, 9, and 14 years, Nwanaji-Enwerem et al showed that children exposed to adverse events were 0.76-year older than children of mothers who did not report these events, in terms of Horvath epigenetic age acceleration ( p = 0.004) ( Nwanaji-Enwerem et al, 2021a ).…”
Section: Pregnancymentioning
confidence: 99%